SURVEI KEADAAN SARANA DAN PRASARANA PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN DI SEKOLAH MENENGAH ATAS NEGERI SE-KABUPATEN JOMBANG - WATI, ROSIANA (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In this study, the researcher uses an instrument PDPJOI which is in the assessment described four aspects, they are: (1) The availability of facilities and infrastructure physical and health education, (2) the availability of sport, health and physical education personnel or teachers, (3) the performance of education units during 2012, (4) accomplishment and awards during 2012. However, in this study described here is only the availability of facilities and infrastructure aspects in sport, health and physical education for Senior high school levels in Jombang. The recapitulation results of data of study in facilities and infrastructure in the senior high school levels in Jombang obtained fair category in score ”C”. The conclusion is that the results obtained for the availability of facilities and infrastructur in sport, health and physical education in Jombang obtain 132 in scores and are categorized into fair category ”C”. This is because there are still some schools in which the availability of land for infrastructure and facilities do not meet the appropriate standards form Decree of eduactional minister No. 24 in 2007. Keywords : The availability of facilities and infrastructure of sport, health and physical education.